The effect of 1,10-phenanthroline on the chromosome damage and sister-chromatid exchanges induced by streptozotocin in mammalian and insect cells - Gonzalez, Marina Cecilia (2000)
The effect of the metal chelating agent 1,10-Phenanthroline (PNT) on the streptozotocin (STZ)-induced chromosomal aberrations (CAs) and sister- chromatid exchanges (SCEs) in Chinese hamster ovary (CHO) and mosquito (Aedes albopictus) cells was investigated. Treatment of CHO and mosquito cells with STZ produced a significant and dose-response increase in the yield of CAs as well as SCEs (p < 0.05). The addition of PNT prevented the induction of CAs by STZ in both types of cells, causing a significant decrease in the frequency of STZ-induced CAs (46.5-72.5%) (p < 0.05). This fact indicates that intracellular transition metals are implicated in STZ-induced CAs and that the Fenton reaction (Fe2+ + H2O2 → OH°+ OH- + Fe3+) is partly responsible for the production of CAs by this compound. On the other hand, the addition of PNT to CHO and mosquito cell cultures did not prevent the induction of SCEs by STZ. Therefore, it is valid to assume that the induction of CAs and SCEs by STZ occurs by different mechanisms.